2005
DOI: 10.1098/rstb.2004.1594
|View full text |Cite
|
Sign up to set email alerts
|

Measuring conditions and trends in ecosystem services at multiple scales: the Southern African Millennium Ecosystem Assessment (SA f MA) experience

Abstract: The Southern African Millennium Ecosystem Assessment (SAf MA) evaluated the relationships between ecosystem services and human well-being at multiple scales, ranging from local through to sub-continental. Trends in ecosystem services (fresh water, food, fuel-wood, cultural and biodiversity) over the period 1990-2000 were mixed across scales. Freshwater resources appear strained across the continent with large numbers of people not securing adequate supplies, especially of good quality water. This translates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(99 citation statements)
references
References 12 publications
(22 reference statements)
4
92
0
3
Order By: Relevance
“…Fourth, there is a clear need expressed in several papers of this volume (and by the Martian consultant) to develop better models describing how the human, biological, physical and chemical components of the Earth system interact (Dobson 2005;van Jaarsveld et al 2005;Watson 2005). Such models, still presently in their infancy, would improve our understanding of the mechanisms by which wild nature affects human wellbeing, and help identify the most effective policy levers for slowing biodiversity loss.…”
Section: )?)mentioning
confidence: 99%
“…Fourth, there is a clear need expressed in several papers of this volume (and by the Martian consultant) to develop better models describing how the human, biological, physical and chemical components of the Earth system interact (Dobson 2005;van Jaarsveld et al 2005;Watson 2005). Such models, still presently in their infancy, would improve our understanding of the mechanisms by which wild nature affects human wellbeing, and help identify the most effective policy levers for slowing biodiversity loss.…”
Section: )?)mentioning
confidence: 99%
“…In order to assess the impact of human land use on South African ecosystems more precisely, the findings presented here could be considerably enriched by further research on the interrelations between our HANPP findings and the rich body of empirical research regarding natural conservation issues that has already been conducted for South Africa (Rouget et al 2003;Scholes and Biggs 2005;VanJaarsveld et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…African countries located in Cirum -Sahara regions are also characterized by water stress brought about by climate variability and wider governance issues [4]. Significant progress has, however, been recorded in some parts of Africa to improve this situation, with urban populations in the southern African region achieving improved water access over recent years [5]. According to one of the most up-to -date studies carried out by [6], the results of the analysis suggested that threats to water security are already the primary cause of some of the most intractable conflict in Africa.…”
Section: Review Of Previous Literaturesmentioning
confidence: 99%
“…A more recent works were carried out by La Barbe and Tapsoba [3] and were also important sources of information. Water access and water resource management are highly variable across the continent [4,5]. African countries located in Cirum -Sahara regions are also characterized by water stress brought about by climate variability and wider governance issues [4].…”
Section: Review Of Previous Literaturesmentioning
confidence: 99%
See 1 more Smart Citation